2020
DOI: 10.1590/s1980-220x2019005403624
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do grupo operativo no ensino do autocuidado com os pés de diabéticos: ensaio clínico randomizado

Abstract: RESUMO Objetivo Avaliar o efeito do grupo operativo no ensino do autocuidado com os pés para prevenção do pé diabético. Método Ensaio clínico controlado e cego, realizado com voluntários que apresentavam Diabetes Mellitus tipo 2, randomizados em grupo tratado (55 pessoas) e grupo controle (54 pessoas). O grupo tratado recebeu a intervenção educativa “Ensino do autocuidado com os pés” e o grupo controle foi somente avaliado. As avaliações dos pés ocorreram antes e após a intervenção, bem como 15 dias depois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 14 publications
0
14
0
11
Order By: Relevance
“…The predominant educational technologies were training sessions in six studies ( 22 , 25 - 26 , 27 , 23 - 20 ) and verbal guidelines, in five ( 19 - 28 , 24 , 29 - 27 ) . It was evidenced that, in five studies, the control groups did not receive any intervention through any educational technology ( 19 , 22 , 21 - 20 ) . The descriptive synthesis of the randomized controlled clinical trials included is presented in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant educational technologies were training sessions in six studies ( 22 , 25 - 26 , 27 , 23 - 20 ) and verbal guidelines, in five ( 19 - 28 , 24 , 29 - 27 ) . It was evidenced that, in five studies, the control groups did not receive any intervention through any educational technology ( 19 , 22 , 21 - 20 ) . The descriptive synthesis of the randomized controlled clinical trials included is presented in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“… Incidence of ulcerations: IG * : I ‡ =0% (0/60) CG † : I ‡ =10% (6/60) Incidence of amputations: IG * : I ‡ =0% CG † : I ‡ =0% There was an improvement in the patients’ knowledge after the intervention (p<0.001). Moreira, et al (2020) ( 21 ) , Brazil. n=109/one month n=55/Illustrative and didactic folder (soft-hard), visual demonstrations (soft-hard), templates (hard), serial album (soft-hard), image projections (hard) and playful drawings (soft-hard).…”
Section: Resultsmentioning
confidence: 99%
“…Dessa forma, percebe-se que a educação se torna o principal instrumento utilizado para promoção de conhecimento e melhora de comportamentos, e consequentemente prevenção de ulcerações (Gomes et al, 2021). E tais atividades educativas são as principais intervenções realizadas pelo enfermeiro, funcionando como ferramentas resolutivas para redução do surgimento de complicações relacionadas a diabetes (Moreira et al 2020). destaca que o enfermeiro deve dispor de conhecimento e habilidades sobre o tema para realizar atividades educativas efetivas e desmitificar crenças populares e instruções inadequadas que o paciente possa deter.…”
Section: Discussionunclassified
“…To test the effectiveness of PedCare, participants with similar sociodemographic and clinical characteristics and lifestyle habits were selected, similar to the results of other studies, where there was a predominance of females, self-reported “pardo” (brown-skinned people/mixed race), married, and family income, number of children, and people living in the household with proportional averages in both groups 20 . Differences in the variables age, personal income, and time attending a health institution were statistically significant between the groups.…”
Section: Discussionmentioning
confidence: 99%